If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12a + 24 = 42 Reorder the terms: 24 + 12a = 42 Solving 24 + 12a = 42 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 12a = 42 + -24 Combine like terms: 24 + -24 = 0 0 + 12a = 42 + -24 12a = 42 + -24 Combine like terms: 42 + -24 = 18 12a = 18 Divide each side by '12'. a = 1.5 Simplifying a = 1.5
| 1/3y=6(3-1/6) | | 0.77r+3=-4 | | (x*x)/(.05-x)=1.7*10^-4 | | 9z-5/z-7 | | 3-7=-7x+-7 | | 12/25y=9/50 | | 3-7=3x+-7 | | 32x-7=15 | | 2a-1+1=4+1 | | -5(10+X)=-55 | | 3n-4n+9=-2 | | -3/4=3-1/2n | | 0.42n-7=5 | | 1=v+8/5 | | 446=q-(235+925) | | N+x=27 | | a+(-27)=(-15) | | 12.88-0.88(x+0.5)=0.25+2(x-3.17) | | 4x+5y+6x-3x+3y= | | https://content.grantham.edu/at/MA105/exams/w2_10.jpg | | 4=60 | | 7+4x=7x+40 | | 2k+-1=2+k | | X^4+11=35 | | 18+7x-9=-27+3x | | -10=(1/4)(8y-12) | | -1x+0.33=0.25 | | 50b+36c= | | x+12=-(13) | | 50b+3c= | | 9+3(3x+5)=24+9x | | 50b+3= |